2021
DOI: 10.1016/j.aucc.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of delirium assessments in critically ill children: A prospective, observational study during routine care

Abstract: Objectives: The objectives of this study was to explore the accuracy of the Cornell Assessment for Pediatric Delirium (CAP-D), Pediatric Confusion Assessment Method for the Intensive Care Unit (pCAM-ICU), and Preschool Confusion Assessment Method for the Intensive Care Unit (psCAM-ICU) when implemented in routine care as delirium screening tools, and to assess patient characteristics and clinical variables that may affect their validity. Design: This is a prospective observational study. Setting: The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…The design of the current study precluded evaluation of the criterion validity of the DIVA Key, and therefore we were unable to determine the sensitivity and specificity, and corresponding positive and negative predictive values, of the DIVA Key in detecting a child’s DIVA status prior to escalation. Given the indicators of DIVA used in the DIVA Key are consistent with other highly sensitive paediatric instruments (e.g., Cornell Assessment of Pediatric Delirium [ 49 , 50 ]), and the results of logistic regression found that first attempt insertion success was lowest in children assessed as high risk of DIVA, however, suggests that the DIVA Key is a promising instrument for the accurate identification of DIVA in this population.…”
Section: Discussionsupporting
confidence: 64%
“…The design of the current study precluded evaluation of the criterion validity of the DIVA Key, and therefore we were unable to determine the sensitivity and specificity, and corresponding positive and negative predictive values, of the DIVA Key in detecting a child’s DIVA status prior to escalation. Given the indicators of DIVA used in the DIVA Key are consistent with other highly sensitive paediatric instruments (e.g., Cornell Assessment of Pediatric Delirium [ 49 , 50 ]), and the results of logistic regression found that first attempt insertion success was lowest in children assessed as high risk of DIVA, however, suggests that the DIVA Key is a promising instrument for the accurate identification of DIVA in this population.…”
Section: Discussionsupporting
confidence: 64%
“…patients were younger (odds ratio [OR] = 1.1; 95% CI 1-1.2) and received any sedation ([OR = 4.1; 95% CI 1.5-11.5) (10). Use of developmental anchor points, not quantified in previous studies, did not improve rater agreement in our study.…”
Section: At the Bedsidecontrasting
confidence: 56%
“…Patients could be assessed on multiple occasions, with at least 3 days in between, to engage as many different nurse raters as possible. We limited the number of assessments per patient to 5, to reduce response bias by overrepresentation of individual subjects (10, 14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study [4], a delirium rate of 69% was found in patients with a length of stay > 48 hrs (37% of the total sample). Delirium in children leads to adverse outcomes, such as complications, falls, prolonged hospital stay, and prolonged mechanical ventilation and even death [5,6]. Delirium also makes it more likely that the child's cognitive, emotional, and social abilities were impaired after discharge, which makes the caregivers suffering [2,4,7].…”
Section: Overview and Research Significancementioning
confidence: 99%